Association between subclinical hypothyroidism and coronary artery disease: Subclinical Hypothyroidism and Coronary Artery Disease - Yaman, Belma; Cerit, Levent; Günsel, Hatice Kemal; Günsel, Aziz; Usalp, Songül; Yüksek, Ümit; Gül, İlker; Cerit, Zeynep; Etikan, İlker; Korkmaz, Aşkın Ali; Duygu, Hamza (Progress in Nutrition, 2019)
Coronary artery disease (CAD) is a common health problem with high morbidity and mortality. In recent years overt hypothyroidism is shown as an independent risk factor of CAD. Thyroid hormones have more effects on the cardiovascular system, and both hypothyroidism and hyperthyroidism have harmful effects on the cardiovascular systemç Subclinical hypothyroidism (SCH) is a common clinical situation with 4-20% frequency. SCH is associated with endothelial dysfunction, coronary atherosclerosis, and cerebrovascular disease. SYNTAX score is the angiographic scoring system and is widely used to evaluate the severity and complexity of CAD. The aim of this study to evaluate the association between SCH and SYNTAX score. This study is a retrospective cohort of participants who undergo coronary angiography and resulted in coronary artery bypass graft surgery. Participants divided into two group according to their SYNTAX score as high SYNTAX score (SYNTAX ≥ 23) and low SYNTAX score (SYNTAX